Motivation and Awareness of Institutional Repositories by Students of Yogyakarta Islamic University of Yogyakarta and Yogyakarta State University - Sembiring, Santana (Record and Library Journal, 2020)
Background of the study: Institutional repositories are considered as one of the appropriate tools used by universities to store, preserve, and disseminate the scientific work of students and lecturers. Open access to institutional repositories allows students to access scientific works openly and they can get more complete parts of the work. However, there is another side of the institutional repository that has not received much attention, namely motivation and awareness about institutional repositories. Supported by data on student access to very high institutional repositories, this research was conducted at two universities in Yogyakarta, UII, and UNY.Purpose: This study aims to find out what motivations UII and UNY students to use institutional repositories and what is the awareness of UII and UNY students about institutional repositories.Method: The method used is qualitative with data collection techniques in the form of interviews with six UII and UNY students obtained based on snowball sampling techniques.Findings: The main motivation of UII students to use institutional repositories is to obtain references while the motivation of UNY students is because the institutional repositories are easy to use tools. In terms of awareness, UII and UNY students have a different awareness about institutional repositories which lie in knowledge, semester, understanding, medium, and willingness to store academic work in institutional repositories.Conclusion: Motivation and awareness are the two main keys that students must possess to succeed in the sustainability of the institution's repository.